Tax efficiency in a model of endogenous markups - Esra Durceylan (SERIEs - Journal of the Spanish Economic Association, 2019)
Efficiency comparison of ad valorem and unit taxes has been traditionally based on consumer welfare. However, if the tax instrument also affects the distribution of firms over their productivities, the policy maker may be concerned about the implications on aggregate productivity as well. This paper makes an efficiency comparison of ad valorem and unit taxes by allowing the distribution of firms to respond to changes in policy. First, I make an efficiency comparison in a model with monopolistically competitive firms that are homogenous with respect to their productivity levels. Consumer preferences exhibit love for variety and allow firms to adjust their markups. I find that ad valorem tax is more efficient. Allowing for firm heterogeneity overturns this result at high revenue requirements. As the tax rate increases, ad valorem tax causes excessive exit of firms which makes the market more competitive. Hence, few surviving firms price lower by decreasing their markups. Lower prices decrease the tax revenue collected. As a result under ad valorem tax regime, higher consumer surplus is dominated by lower tax revenue. On the other hand, production is concentrated among relatively more productive firms. Thus, aggregate productivity is higher under ad valorem tax regime.
Keywords: L11; H21; H25; 330; Unit tax; Ad valorem tax; Efficiency; Monopolistic competition; Heterogenous firms